Microwave-assisted pretreatment of lignocellulosic biomass: a review - Ethaib, Saleem; Omar, Rozita; Mustapa Kamal, Siti Mazlina; Awang Biak, Dayang Radiah (2014)
Lignocellulosic biomass is an abundant biopolymer in nature as a by-product of agricultural industry which offers a cheap source of sugar and bio-alcohol. The production of bio-alcohol from lignocellulosic wastes requires pretreatment, hydrolysis and fermentation steps. Pretreatment technologies are aimed to break down the recalcitrant structure of lignocellulosic biomass and release the fermentable sugar in the extraction of sugar process for bio-alcohol production. Microwave-based pretreatment has been considered as one of the promising methods of pretreatment, utilising thermal and non-thermal effects that drive physical, chemical or biological reactions. The advantages of microwaveassisted process such as in waste treatment and food drying by reducing the plant footprint, higher throughput, higher reaction rates, higher yield and purity have increased more interest of late. This paper reviews the recent application of microwave-assisted pretreatment of lignocellulosic material via the combination of microwave pretreatment with other physical and chemical pretreatment methods. The synergistic effect of microwave-assisted pretreatment with other pretreatment methods could enhance the fermentable sugar yield from various feedstocks. Different operating parameters that govern the reducing sugar yields such as biomass loading, microwave intensity, and irradiation time are presented. Formation of inhibitor compounds during microwaved-assisted pretreatment are also discussed.